Assessment of Augmented Reality Technology's Impact on Speed of Learning and Task Performance in Aeronautical Engineering Technology Education. Issue 3 (3rd July 2021) - Borgen, Kristoffer B.; Ropp, Timothy D.; Weldon, William T.
ABSTRACT: Objective : This study compared learning and skill transfer among university aviation students using interactive Augmented Reality (AR) technology versus traditional paper-based instruction. While similar AR use and research in university education exists, this study piloted a comparative method assessing knowledge retention and transfer. Background : AR technology is a popular tool used in technical education. But learner behaviors observed like game play and exploration during this study could impact future learning strategy design as AR use increases. Method : 36 university undergraduate students enrolled in a university aeronautical engineering technology program were divided into AR and paper-based groups and compared on first-time task execution times for starting an aircraft auxiliary power unit (APU). A two-sample Kolmogorov-Smirnov test comparing times for task completion was used. Results : Learner task times using AR were consistently faster, replicating similar AR studies, compared to learners using paper-based. However, AR test subjects also took longer interacting with the technology, including gaming-style "play" and exploration of the digital twin AR flight deck environment. This is believed to enhance learner innovation, knowledge retention and transfer, warranting further study. Conclusion : AR users had significantly reduced task execution times. Pre-task "gamification and play" were also observed among the AR users, which could impact how educators and the industry assess and leverage learning strategies when using AR for job task training.